2011
DOI: 10.1111/j.1365-2230.2011.04106.x
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytoid and signet-ring cell carcinoma of the axilla: a type of cutaneous apocrine carcinoma equivalent to histiocytoid lobular carcinoma of the breast?

Abstract: There is a histopathological similarity between cutaneous apocrine carcinoma (CAC) and breast carcinoma. Cutaneous histiocytoid or signet-ring cell (SRC) carcinoma is a rare neoplasm, which usually occurs on the eyelid, and less commonly on the axilla. The precise histogenesis of this carcinoma remains controversial. We report the case of a man with a cutaneous histiocytoid SRC carcinoma of the axilla having histopathological and immunohistochemical features that were quite similar to histiocytoid lobular carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 10 publications
2
50
0
Order By: Relevance
“…Moreover, overexpression of HER2 indicates poor prognosis with shortened disease‐free and overall survival in breast cancer. PSRCHC of the eyelid has usually been negative for HER2 expression, 1 while PSRCHC of the axilla has been positive 3 . In our case, HER2 protein was overexpressed, but the gene was not amplified.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Moreover, overexpression of HER2 indicates poor prognosis with shortened disease‐free and overall survival in breast cancer. PSRCHC of the eyelid has usually been negative for HER2 expression, 1 while PSRCHC of the axilla has been positive 3 . In our case, HER2 protein was overexpressed, but the gene was not amplified.…”
mentioning
confidence: 50%
“…Misago et al. 3 suggested that axillary PSRCHC would be a type of cutaneous apocrine carcinoma, which is equivalent to histiocytoid lobular carcinoma of the breast.…”
mentioning
confidence: 99%
“…In patients that present with positive regional lymph nodes, lymphadectomy, in addition to the removal of the primary, is common treatment among the PCAC literature [2,3,15,[20][21][22][23]. Radiotherapy may also provide additional benefit among those with regional lymph node metastases; however data is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Primary signet‐ring cell/histiocytoid carcinoma has been described in few scattered case reports in the literature. About 20 cases have been reported involving the eyelid and only five cases have been reported previously involving the axilla . Whether this neoplasm is of apocrine or eccrine origin has remained a source of debate .…”
Section: Discussionmentioning
confidence: 99%
“…Primary signet‐ring cell/histiocytoid carcinoma (hereafter, cutaneous signet‐ring cell carcinoma) represents an extremely rare adnexal neoplasm that most frequently not only presents on the eyelid but has also been reported to present within the axilla . Because of its histopathologic similarity to lobular carcinoma of the breast as well as other metastatic carcinomas with signet‐ring cells such as signet‐ring cell adenocarcinoma of the stomach, lung or prostate, a comprehensive workup for other primary sources of carcinoma is often required prior to definitive diagnosis of cutaneous signet‐ring cell carcinoma …”
mentioning
confidence: 99%